ALDH1A3‐mTOR axis as a therapeutic target for anticancer drug‐tolerant persister cells in gastric cancer. Issue 3 (11th February 2020) - Kawakami, Ryuhei; Mashima, Tetsuo; Kawata, Naomi; Kumagai, Koshi; Migita, Toshiro; Sano, Takeshi; Mizunuma, Nobuyuki; Yamaguchi, Kensei; Seimiya, Hiroyuki
Abstract: Tumors consist of heterogeneous cell populations that contain cancer cell subpopulations with anticancer drug‐resistant properties called "persister" cells. While this early‐phase drug tolerance is known to be related to the stem cell‐like characteristic of persister cells, how the stem cell‐related pathways contribute to drug resistance has remained elusive. Here, we conducted a single‐cell analysis based on the stem cell lineage‐related and gastric cell lineage‐related gene expression in patient‐derived gastric cancer cell models. The analyses revealed that 5‐fluorouracil (5‐FU) induces a dynamic change in the cell heterogeneity. In particular, cells highly expressing stem cell‐related genes were enriched in the residual cancer cells after 5‐FU treatment. Subsequent functional screening identified aldehyde dehydrogenase 1A3 (ALDH1A3) as a specific marker and potential therapeutic target of persister cells. ALDH1A3 was selectively overexpressed among the ALDH isozymes after treatment with 5‐FU or SN38, a DNA topoisomerase I inhibitor. Attenuation of ALDH1A3 expression by RNA interference significantly suppressed cell proliferation, reduced the number of persister cells after anticancer drug treatment and interfered with tumor growth in a mouse xenograft model. Mechanistically, ALDH1A3 depletion affected gene expression of the mammalian target of rapamycin (mTOR) cell survival pathway, which coincided with a decrease in the activating phosphorylation of S6 kinase. Temsirolimus, an mTOR inhibitor, reduced the number of 5FU‐tolerant persister cells. High ALDH1A3 expression correlated with worse prognosis of gastric cancer patients. These observations indicate that the ALDH1A3‐mTOR axis could be a novel therapeutic target to eradicate drug‐tolerant gastric cancer cells. Abstract : Using a single‐cell analysis of patient‐derived gastric cancer cells, we identified aldehyde dehydrogenase 1A3 (ALDH1A3) as a therapeutic target of anticancer drug‐tolerant persister cells. ALDH1A3 knockdown significantly suppressed cell proliferation and reduced the number of persister cells after treatment with 5‐fluorouracil (5‐FU) and SN38. Mechanistically, ALDH1A3 depletion downregulated the mTOR cell survival pathway, and an mTOR inhibitor reduced the number of drug‐tolerant persister cells.